Influence of Contact Experience and Germ Aversion on Negative Attitudes Toward Older Adults: Role of Youth Identity - Shimizu, Yuho; Hashimoto, Takaaki; Karasawa, Kaori (Frontiers in Psychology, 2022)
The world’s population is currently aging, and the issue of ageism has become serious worldwide, including in Japan. Negative attitudes toward older adults can have undesirable effects on the mental and physical health of this group. We focused on the effects of contact experience with older adults and germ aversion, or the degree of aversion to infection, on negative attitudes toward older adults. Additionally, we included a moderating variable; youth identity, or the sense of belonging with younger rather than older age groups. An online survey was conducted with Japanese participants (N = 603). We conducted multiple regression analyses and the results showed that the interaction effect between youth identity and contact experience on negative attitudes toward older adults was significant. The findings suggest that contact experience may help in reducing negative attitudes toward older adults among people with low youth identity. The interaction effect between youth identity and germ aversion, however, was not significant. Academic research on the effects of some psychological interventions (e.g., intergenerational social exchange) should pay particular attention to the role of youth identity. Future directions for empirical studies are also discussed.